UJI EFEK ANALGETIK EKSTRAK ETANOL DAUN NANGKA (Artocarpus heterophyllus Lam.) TERHADAP MENCIT (Mus musculus) YANG DIINDUKSI ASAM ASETAT - Auliah, Nielma; Lotuconsina, Ari Aprianto; Thalib, Muthmainnah (Jurnal Riset Kefarmasian Indonesia, 2019)
Research has been carried out with the title "Test of the Analgetic Effect of Ethanol Extract of Jackfruit Leaves (Artocarpus heterophyllus Lam.) On Acetic Acid-induced Mice (mus musculus). Analgesics or painkillers are drugs that reduce or eliminate taste without losing consciousness. One of the traditional plants commonly used empirically is jackfruit leaves (Artocarpus heterophyllus Lam.). This study aims to determine the analgetic effect of ethanol extract of jackfruit leaves (Artocarpus heterophylus Lam.) At a dose of 100 mg / kgBB, 300 mg / kgBB and 600 mg / kgBW on acetic acid induced male mice (Mus musculus). This research is an experimental study and uses the chemical induction method. The results obtained in the form of% protection inhibition stretching ethanol extract of jackfruit leaves (Artocarpus heterophyllus Lam.) At a dose of 100mg / kgBB (28.79%); 300mg / kgBB (53.31%); 600mg / kgBB (60.70%). From the results of the research that has been done it can be concluded that the ethanol extract of jackfruit leaves (Artocarpus heterophyllus Lam.) Has the highest analgesic effect at a dose of 600mg / kgBW having a percentage of protection of 66.70%.